Ultra high performance concrete (UHPC) sleeper: Structural design and performance. (1st May 2020) - Bae, Younghoon; Pyo, Sukhoon
Highlights: Ultra high performance concrete (UHPC) is firstly adopted to railway sleeper. A structural design is carried out to fully utilize the material benefits of UHPC. Ductile nature of UHPC results in stable structural behavior and outstanding crack resistance. This study provides new insight into the structural applications of UHPC under railway loading. Abstract: Both structural and material performance of railway sleepers are critical to ensure the safety of railway track structures. In this study, for the first time, ultra high performance concrete (UHPC) is adopted to the post-tensioning type of sleeper to prolong design life and reduce the maintenance of sleepers. A structural design is carried out to fully utilize the material benefits of UHPC, including superior compressive strength and tensile ductility, and reviewed the critical sections of the sleeper based on strain compatibility analysis. Sixteen UHPC sleepers were fabricated using the developed UHPC mixture, incorporating coarser aggregates and ground granulated blast furnace slag, to perform structural verification tests according to the European standard, including bending strength tests under static, dynamic, and fatigue loading. The series of structural tests conducted on the UHPC sleepers show that the ductile characteristic of UHPC reinforced with steel fibers resulted in stable structural behavior and outstanding crack resistance capabilities even after the initial cracks developed. This experimental study may provide new insight into the structural applications of UHPC under railway loading conditions.